Kriminalisasi Sekstorsi dalam KUHP 2023: Urgensi Pengaturannya - Nurhaliza, Eva; Zakaria, Alfons (RechtJiva, 2026)
Sexual extortion (sextortion) is a crime combining extortion and sexual violence through abuse of power to coerce victims into sexual services. Despite its serious impact on human dignity and public trust, Indonesia's criminal law, including the 2023 Criminal Code, has not explicitly regulated sextortion as a separate offense, creating legal impunity for perpetrators and inadequate victim protection. This study analyzes the urgency of regulating sextortion and formulates an ideal legal provision through comparative study. Using normative juridical methods with statutory, comparative, and conceptual approaches, this research examines primary materials from Indonesian laws and secondary materials from Alabama Code § 13A-6-241 and Arkansas Code § 5-14-113. The findings reveal three fundamental urgencies: protecting human dignity from non-physical coercion, preventing exploitation of power asymmetry, and establishing clear legal boundaries between extortion and sexual violence. Based on comparative analysis, the ideal formulation must adopt objective elements including threats to compel sexual acts by exploiting power relations, along with subjective elements of perpetrator intent. The offense should be categorized as an ordinary crime with proportional criminal sanctions to protect victim dignity and prevent sexually motivated abuse of power.